Black Box of Interpreting: Hidden under Your Nose? A Study of Shift as the Product of Black Box Based on Tag Gameshow of Youtube - Karsten, Sebastian; Putri, Siegfrieda A. S. Mursita (Universitas Sanata Dharma, 2018)
Translating according to Nida is more about the understanding the concept of translation, in this study the main aims is that to dive deeper into the art of interpretation, another branch of translation. According to Hudson, (2005) Translation as for most people know, is an act of changing Source Language and deliver it into Target Language, so that people who are not a native to it, might understand the point of information itself. Translation and interpretation holds a lot of mysteries, this is the fact that triggers this study to be conducted. This study observes one of Interpretation product made from black box.Â The black box theory produced by Englund Dimitrova & Tiselius (2016) is investigated in this study. It also applies interpreting shift proposed by Catford (1965) as the indicators and the products or result of the occurrence of black box and also combined with the techniques applied by the interpreter. The data were fifteen videos from Tara Arts Game Indonesia YouTube channel. The source language from the conversation inside the game and interpreting version were analyzed and then classified into three major classes of shifts to prove the indication that shift is a product of black box. This was a mixed quantitative and qualitative study and also a primary research. The result of this research is that the black box phenomenon is real, triggered by working memory and adjustment as proposed by Baddeley & Hitch (1974). Meanwhile, the major types of shift found are unit shift, level shift, form 3 and omission.Â Keywords: Black Box, Shift, Working MemoryÂ